CAR‐NK cells: the next wave of cellular therapy for cancer. Issue 4 (28th April 2021) - Daher, May; Melo Garcia, Luciana; Li, Ye; Rezvani, Katayoun
Abstract: T cells engineered to express chimeric antigen receptors (CARs) have revolutionised the field of cellular therapy for cancer. Despite its success, this strategy has some recognised limitations and toxicities. Hence, there is growing interest in developing novel cellular therapies based on non‐αβ T‐cell immune effector cells, including NK cells that offer clear advantages in cancer immunotherapy. As a result, NK cells are being explored as an alternative platform for CAR engineering and are becoming recognised as important players in the next generation of cellular therapies targeting cancer. In this review, we highlight preclinical and clinical studies of CAR‐NK cells derived from different sources and discuss strategies under investigation to enhance the antitumor activity of these engineered innate immune cells. Abstract : NK cells can be derived from various sources (PB, UCB, HSC, iPSC, NK cell lines) and can be engineered to express a chimeric antigen receptor (CAR) to target various surface antigens on cancer cells. These CAR‐NK cells can be used as off‐the‐shelf adoptive cellular therapy to treat patients with various malignancies.